BVRI - OBSERVATION OF AGN NGC 4151 IN 2009-2011 - Artamonov, B.; Oknyanskij, V.; Ezhkova, O.; Metlova, N. (Одеські астрономічні публікації, 2013)
The observation of AGN NGC 4151 was completed in BVRI filters on1.5 metertelescope of Maidanak observatory and Zeiss-600 telescope of Crimean laboratory SAI in 2009-2012. We made photometric processing of obtained CCD frames and presented the result in pictures.